MANAJEMEN PROGRAM KEAGAMAAN DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI MTS AN NAJAH PEKANBARU - Dela Anggraini; Hadisty Sa’adatul Aisy; Helwina Nur Fadilla (STKIP Pesisir Selatan, 2026)
This study aims to analyze the management of religious programs in shaping students’ religious character at MTs An Najah Pekanbaru. The research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the principal, vice principals, Islamic Education teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the management of religious programs at MTs An Najah Pekanbaru is implemented through integrated stages of planning, organizing, actuating, and controlling. The religious programs are designed based on the madrasah’s vision and mission, organized through clear role distribution, implemented continuously through habituation and teachers’ role modeling, and monitored through regular supervision and evaluation. Supporting factors include the commitment of madrasah leadership, active teacher involvement, and a religious school culture, while inhibiting factors include limited human resources, diverse religious backgrounds of students, and limited implementation time. These findings indicate that well-planned and sustainable religious program management plays a role in shaping students’ religious character.